(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Azo dyes, like Remazol Black B, form covalent bonds with textile fibers like cotton, setting them apart from traditional dyes. Due to their advantageous qualities of vivid color, water resistance, straightforward application processes, and low energy consumption, they are widely used in the textile industry. Major environmental effects of their discharge into receiving streams include reduced photosynthesis in aquatic life as a result of decreased light penetration. Seven isotherm models—Henry, Langmuir, Freundlich, BET, Toth, Fritz-Schlunder IV, and Fritz-Schlunder V—were used to analyze the biosorption isotherm data of Remazol Black B dye biosorption by Aspergillus flavus and were fitted using non-linear regression. Based on statistical analysis, the Fritz-Schlunder IV was determined to be the best model using root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF), corrected AICc (Akaike Information Criterion), Bayesian Information Criterion (BIC), and Hannan-Quinn information criterion (HQC). The calculated Fritz-Schlunder IV parameter, bFS value was found to be 3.812 mg/g (95% confidence interval of 0.312 to 7.311) and qmFS value of 0.0224 (95% confidence interval of -21725.002 to 21725.047).